Teori Munculnya Religi (Tinjaun Antropologis Terhadap Unsur Kepercayaan Dalam Masyarakat) - Nasruddin Nasruddin (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2013)
Religion deals with human attempts to measure the meaning of their own existence and of the universe. Religion can awaken the most perfect inner happiness, the feelings of fear, and horror, although religion directed entirely to the world that not viewable (the hereafter), but religion also involves itself in matters of everyday in this world. Religion is a source of images of the world that it should be; images can repeatedly reinterpreted to evaluate the social patterns of the new even unexpected. Permanence of religion relates to its ability to continuously adjust its highest level descriptions of situations as well as new forms of criticism. Some experts try to give arguments about the existence of religion or relegi of way/different viewpoints that gave birth to the various shades of opinion, but it can be concluded that a person's religiousness is influenced by two factors: external and internal.